2023
DOI: 10.1007/s43390-023-00653-6
|View full text |Cite
|
Sign up to set email alerts
|

Reducing radiation exposure and cancer risk for children with scoliosis: EOS the new gold standard

Abstract: Purpose Children are exposed to significant radiation doses during the investigation and treatment phases of scoliosis. EOS is a new form of low-dose radiation scan which also yields great image quality. However, currently its use is discouraged in the UK due to higher costs. We aimed to quantify the additional radiation dose and cancer risk. Methods We retrospectively reviewed all paediatric cases who received both standing whole spine roentgenograms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It has been shown that image quality of a properly acquired conventional digital radiograph exceeds that of EOS [5]. Nonetheless, the substantial radiation dose reduction which can be achieved by EOS compared to conventional whole body radiography must be also emphasized, as it has been shown that the latter results in a 5.4-fold increase in lifetime cancer risk in the paediatric population [18].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that image quality of a properly acquired conventional digital radiograph exceeds that of EOS [5]. Nonetheless, the substantial radiation dose reduction which can be achieved by EOS compared to conventional whole body radiography must be also emphasized, as it has been shown that the latter results in a 5.4-fold increase in lifetime cancer risk in the paediatric population [18].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the acquisition costs for an X-ray machine that can only be used for whole-body images are a concern [ 9 ]. Although Rose et al showed more than five times lower radiation exposure compared to standard X-rays of the spine, the advantages do not seem to justify the high costs [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, Simons et al found no significant measurement differences between EOS imaging and routine radiographs, with high intraobserver and interobserver reliability 9 . Although initial studies raised questions regarding the cost benefits of EOS scans 10 , recent research demonstrated a significant 5.4-fold increase in cancer risk with standard imaging compared with EOS whole-spine monitoring in children 11 . Although widespread adoption of EOS, particularly outside of major academic institutions, is a considerable goal yet to be attained, we anticipate progressive implementation because of its significant benefits, one of which includes the elimination of stitching errors.…”
Section: Discussionmentioning
confidence: 99%